2014
DOI: 10.3109/13816810.2014.907920
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Findings in Patients with the Hermansky-Pudlak Syndrome (Types 1 and 3)

Abstract: Purpose To describe and compare ocular findings in patients with Hermansky-Pudlak syndrome (HPS) type 1 and 3. Methods This is a retrospective case series of 64 patients with HPS from 1999 to 2009 evaluated at an outpatient private ophthalmologic clinic. Patients underwent genetic analysis of selected albinism (Tyrosine and P gene) and HPS genes (HPS-1 and HPS-3) by screening for common mutations and exon sequencing with DNA screening. Descriptive and a non-parametric statistical analysis were done. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…In the present study, the proband with HPS3 showed a very mild decrease in visual acuity, so these findings correspond to previous studies. Meanwhile, our study showed similar results in iris transillumination examination [23]. As previously reported, patients with HPS type 3 had less iris transillumination than patients with HPS type 1 [24].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, the proband with HPS3 showed a very mild decrease in visual acuity, so these findings correspond to previous studies. Meanwhile, our study showed similar results in iris transillumination examination [23]. As previously reported, patients with HPS type 3 had less iris transillumination than patients with HPS type 1 [24].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported that different types of HPS patients showed various degrees of visual impairment. Visual impairment is usually less severe in patients with HPS type 3 than in those with HPS type 1 [ 23 ]. In the present study, the proband with HPS3 showed a very mild decrease in visual acuity, so these findings correspond to previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The slit lamp examination is part of the comprehensive ophthalmologic evaluation in patients with HPS. 76 This test provides a three-dimensional view of the eye components to document the present of abnormalities. Additional findings during an ophthalmologic visit may include iris transillumination, fundus hypopigmentation, presence of nystagmus, and decreased visual acuity.…”
Section: Ophthalmologic Examinationmentioning
confidence: 99%
“…Periodic alternating Nystagmus is always present in these patients. Strabismus is a common finding in all forms of albinism-esotropia or exotropia [15]. Our patient has periodic alternating nystagmus and exotropia.…”
Section: Discussionmentioning
confidence: 97%